INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON THE DECISION OF BUYING AYAM PENYET SURABAYA IN MEDAN - Ginting, Samuel Tenang Ukur Ardianta; Siringo Ringo, Adinda Kristin (Jurnal Apresiasi Ekonomi, 2021)
This study aims to determine and show the quality of product and service quality on Ayam Penyet Surabaya in Medan have a significant effect on consumer purchasing decisions. The research methodology used is a quantitative approach. The sample used is the customer as many as 99 respondents. Sources of primary data obtained by using a questionnaire or questionnaire, for the variable product quality 10 statement items, service quality variable 10 statement items, and the purchase decision variable 8 statement items, all statements are valid and reliable. Secondary data in the form of data relating to the products offered and services to consumers. Analysis of the data used in this study is multiple linear regression test, classical assumption, multicollinearity, heteroscedasticity, determinant, t test and f test with the help of SPSS version 24.0. The significant level of product quality is 0.028 <0.05, service quality is 0.000 <0.05, with a Sig value of <0.05. From the determination test, it is known that the percentage of the influence of product quality and service quality variables on the purchasing decision variable is 0.460 or 46.0%, while the remaining 54.0% is influenced by other variables.Â Keyword: Product Quality, Service Quality, Purchase Decision.